A Threshold Dosage of Testosterone for Female‐to‐Male Sex Reversal in Rana rugosa Frogs. Issue 8 (28th September 2016) - Oike, Akira; Kodama, Maho; Nakamura, Yoriko; Nakamura, Masahisa
ABSTRACT: Androgens play a critical role in testicular differentiation in many species of vertebrates. While female‐to‐male sex reversal can be induced by testosterone (T) in some species of amphibians, the mechanism still remains largely unknown even at the histological level. In this study, we determined a threshold dosage of T to induce female‐to‐male sex reversal in the Japanese frog Rana ( R .) rugosa . Tadpoles were allowed to metamorphose into frogs with T present in the rearing water. At 0.2 ng/mL T, female frogs formed tissue comprising a mixture of ovary and testis, the so‐called ovotestis, the size of which was significantly smaller than the wild‐type ovary. Histological changes occurring in the oocytes of T‐treated ovaries induced oocyte degeneration in the masculinizing ovaries leading to their final disappearance. In parallel, many germ cells emerged in the cortex of the ovotestis and, later, in the medulla as well. RT‐PCR analysis revealed upregulated expression of CYP17 and Dmrt1 but not 17βHSD in the ovotestis, and downregulation of Pat1a expression. Furthermore, immunohistology revealed CYP17‐positive signals in the cortex of the masculinizing ovary, spreading throughout the whole area as the testis developed. These results indicate that oocytes are sensitive to T in the ovary of R. rugosa and that male‐type germ cells expand in the masculinizing gonad (testis) contemporaneous with oocyte disappearance.